Energy Consumption-sensitive Intentional Rerouting of Protected Connections in Elastic Optical Networks - ANOH, Nogbou Georges; KOBENAN, Ali Ouattara; ADEPO, Joel Christian; BABRI, Michel; KORA, Ahmed Dooguy (International journal of computer network and information security, 2024)
The reduction of energy consumption in elastic optical networks is of major interest to the research community. As a result, several methods for solving this problem in combination with existing classical problems have been proposed. Elastic optical networks are subject to disturbance phenomena that degrade their quality and performance. To optimize resources, operators must recalculate new routes and plan the displacement of established connections towards these new routes to cope with these phenomena, it’s the reconfiguration. The problem addressed in this article is to reconfigure a set of unicast protected connections without interruption to a new routing calculated during the process. Knowing that the use of backup paths solves the interruption problem, but has an impact on the overall energy consumption, the goal is to find a good compromise between the two sub-problems when switching from old routes to new ones. To the best of our knowledge, there is no work on reconfiguration that uses energy-aware backup paths. In this work, we proposed an energy-aware EERA_EON rerouting algorithm using the backup paths. Simulations have shown the performance of this approach in terms of energy consumption compared to the work of our predecessors. Subsequently, we proposed a classical BRA_EON rerouting algorithm in elastic optical networks. Simulation results show that we perform BRA_EON in terms of the number of steps.